The use of table tennis funds' in the curse of the students' physical education. - Zacharina E.A; Globa T.A (Kharkov National Pedagogical University, 2011)
The opportunity of the usage of funds of the table tennis is considered during the movement education classes. The authors develop and settle down by experiment the content of the classes with top-priority usage of the funds of table tennis. The influence on the level of the somatic health, the physical fitness and the students' working capacity was defined. In experiment took part 60 students of 1 year studying. Physical activity of students estimated by the test PWC170.